Impact of the COVID-19 pandemic on Gastroenterology Divisions in Italy: A national survey. Issue 8 (August 2020) - Maida, M.; Sferrazza, S.; Savarino, E.; Ricciardiello, L.; Repici, A.; Morisco, F.; Furnari, M.; Fuccio, L.; Morreale, G.C.; Vitello, A.; Burra, P.; Marchi, S.; et al.
ABSTRACT: Background: In Italy, the spread of the COVID-19 pandemic has stressed the entire healthcare system and required a huge re-organization of many Divisions, including those of Gastroenterology. Aims: to assess the impact of COVID-19 pandemic on Gastroenterology Divisions across Italy. Methods: All members of the Italian Society of Gastroenterology (SIGE) were invited to answer a web-based survey. Results: Data of 121 hospitals from all 20 Italian regions were analyzed. Overall, 10.7% Gastroenterology Divisions have been converted to Covid Units. Outpatients consultations, endoscopic and ultrasound procedures were limited to urgencies and oncology indications in 85.1%, 96.2% and 72.2% of Units, respectively, and 46.7% of them suspended the screening for colorectal cancer. Moreover, 72.2% of the staff received a training for use of personal protective equipment, although 45.5% did not have sufficient devices for adequate replacement. Overall, 132 healthcare workers in 41 Gastroenterology Divisions were found to be infected. Conclusion: This is the first study to evaluate, at a country level, the impact of COVID-19 outbreak on Gastroenterology Divisions. Substantial changes of practice and reduction of procedures have been recorded in the entire country. The long-term impact of such modifications is difficult to estimate but potentially very risky for many digestive diseases.